1974
DOI: 10.1128/iai.10.4.750-756.1974
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of Progenitor Toxins of Clostridium botulinum Type B

Abstract: Purification of progenitor toxin of Clostridium botulinum type B strain Okra was undertaken by sequential steps of acid precipitation, extraction, ammonium sulfate precipitation, ribonuclease digestion, acid precipitation, protamine treatment, sulphopropyl-Sephadex chromatography, and Sephadex G-200 gel filtration. Two different molecular-sized toxins, named large (L) and medium (M) toxins, were obtained. L toxin was centrifugally homogeneous but electrophoretically heterogeneous. It contained 2.5 x 108 to 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
4

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 18 publications
5
50
0
4
Order By: Relevance
“…Type B progenitor toxin was prepared by a previously published method (16). The neurotoxin was purified by DEAE-Sephadex A-50 (Pharmacia, Uppsala, Sweden) chromatography and converted to toxoid by dialysis against 0.1 M phosphate buffer, pH 7.0, containing 0.4% Formalin (14,17). The purified neurotoxin proved to be unnicked by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (18).…”
Section: Methodsmentioning
confidence: 99%
“…Type B progenitor toxin was prepared by a previously published method (16). The neurotoxin was purified by DEAE-Sephadex A-50 (Pharmacia, Uppsala, Sweden) chromatography and converted to toxoid by dialysis against 0.1 M phosphate buffer, pH 7.0, containing 0.4% Formalin (14,17). The purified neurotoxin proved to be unnicked by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (18).…”
Section: Methodsmentioning
confidence: 99%
“…The existence of heterogenously molecular-sized purified type . A and B toxins, 12, 16 and 19s for type A , and 1 2 and 1 6 s for type B (Kozaki et al 1974) have been demonstrated. Type E and F toxins were reported t o be uniform in molecular size, at 12 and lOS, respectively (Kitamura et a / .…”
Section: Introductionmentioning
confidence: 90%
“…Type B strains produce both 12 and 16s toxins in culture (Kozaki et al 1974). Schantz and Spero (1967) reported that type A strains produce 1 9 s toxin only in culture, whereas Sugii and Sakaguchi (1975) demonstrated that they produce only 12s toxin in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Nonproteolytic strains of types B, E, and F are known to produce toxins that are activated upon trypsinization (2,3,5). The progenitor toxin of a proteolytic type B strain Okra was obtained in two different molecular forms, 16S (L toxin) and 12S (M toxin) (9). Both L and M toxins consist of neurotoxic and nontoxic components.…”
mentioning
confidence: 99%
“…The neurotoxic component of either toxin has a molecular weight of 170,000 (7S) (1,8). The nontoxic component of L toxin is about 12S and contains hemagglutinin activity, whereas that of M toxin is 7S and contains no hemagglutinin activity (9).…”
mentioning
confidence: 99%